Managing monetary policy facing U.S. external constraint and internal macroeconomic divergences: The case of the Western European Central Banks in the 1980s - Alexandre Reichart (The Journal of European Economic History (JEEH), 2024)
This paper offers a narrative description of Western European monetary policies during the 1980s, seen from a French and European perspective and based on the archives of the General Council of the Bank of France and of the Committee of Governors (CoG) of the central banks of the member states of the European Economic Community. We show that the external constraint faced by Western European central banks in the 1980s was composed of three factors. Western European monetary authorities had limited flexibility at that time, as the "direct" and "indirect influences" of the U.S. monetary policy, as well as macroeconomic divergences between France and West Germany, deeply restrained monetary policies. We show that European central banks were constrained by the evolution of the U.S. monetary policy ("direct influence"), by the variations of the U.S. exchange rate and their consequence on the German Mark exchange rate within the European Monetary System ("indirect influence"), and by the inflation rate differential between France and West Germany, which was the most important of the "internal macroeconomic imbalances". We also underline the evolution of these three elements of external constraint throughout the decade.
Keywords: 330; Monetary policy; Central bank; Inflation; Exchange rate; German mark; US dollar; Narrative method; EU states; USA; Geldpolitik; Zentralbank; Inflation; Wechselkurs; Deutsche Mark; US-Dollar; Narrative Methode; EU-Staaten; USA